The Effectiveness of Radio and TV Educational Programs in Adult Education in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Adult education plays a crucial role in national development, yet Nigeria faces significant challenges in achieving widespread literacy and lifelong learning. This study examines the effectiveness of radio and TV educational programs in promoting adult education in Nigeria, considering accessibility, engagement, and learning outcomes. Despite technological advancements, broadcast media remains a vital tool for reaching non-literate and rural populations. Using a mixed-methods approach, this paper analyzes existing programs, learner participation rates, and policy frameworks supporting educational broadcasting. Findings suggest that while radio and TV programs have improved knowledge dissemination, challenges such as inconsistent scheduling, limited interactivity, and funding constraints hinder optimal effectiveness. The study recommends enhancing program design, increasing government and private sector investment, and integrating digital platforms for hybrid learning. The insights from this research contribute to strategies for scaling adult education through mass media in Nigeria and similar developing contexts.